Engineering materials and tribology XXV selected, peer reviewed papers from the 25th International Baltic Conference on Engineering Materials & Tribology, (BALTMATTRIB), November 3-4, 2016, Riga, Latvia - Loca, Dagnija (Key engineering materials, 2017)
The book "Engineering Materials and Tribology XXV" published by results of 25th International Baltic Conference of Engineering Materials and Tribology (November 3-4, 2016, Riga, Latvia) and cover the latest findings in the fields of advanced materials: materials for energy and environmental applications, biomaterials, materials characterization, hybrid materials, functional materials and structural materials, polymers and composites, ceramics, powder materials and powder metallurgy technology, coatings, surface engineering and latest researches and solutions in the area of tribology. We hope this collection will be useful for wide range of scientists and engineers in their activity.